The determinants of global bank credit-default-swap spreads - Iftekhar Hasan; Liuling Liu; Gaiyan Zhang (Bank of Finland, 2014)
Using a sample of 161 global banks in 23 countries, we examine the applicability of structural models and bank fundamentals to price global bank credit risk. First, we find that variables predicted by structural models (leverage, volatility, and risk-free rate) are significantly associated with bank CDS spreads. Second, some CAMELS indicators, including asset quality, cost efficiency, and sensitivity to market risk, contain incremental information for bank CDS prices. Moreover, leverage and asset quality have had a stronger impact on bank CDS since the onset of the recent financial crisis. Banks in countries with lower stock market volatility and/or more financial conglomerates restrictions tend to have lower CDS spreads. Deposit insurance appears to have an adverse effect on CDS spreads, indicating a moral hazard problem.
URN:NBN:fi:bof-201501051001
Keywords: G21; G13; G15; 330; bank credit default swaps; structural models; CAMELS; global banks